The intersection of Islam and Confucianism in Khaled Hosseini's The Kite Runner: a philosophical analysis through the lens of Neo-Confucianism - Ningjie, Dong; Shohana Hussin (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explores the intersection between Islam and Confucianism by analysing the protagonist Aamir's development and salvation in Khaled Hosseini's novel, The Kite Runner, through the lens of Neo-Confucianism. This interdisciplinary approach broadens the scope of this intersection from religion to literature. This study examines the shared ideals and objectives of both civilizations, namely that kindness is innate to the human race and that becoming good is humanity's ultimate objective. This study adopts Zhang Zai's philosophical approach as the theoretical foundation to analyse Aamir's path to atonement, focusing on the epistemological propositions of "sincerity" and "changing temperament." The discussion centres on the three fundamental steps of self-redemption, namely acknowledgement of sins, confession, and redemption, and how Aamir achieves self-redemption by "changing temperament" under the guidance of "sincerity." Through this analysis, it demonstrates that Zhang Zai's ideas can be used to comprehend Islamic literary works with a redemption theme and present a new dimension to the study of Zhang Zai's philosophy. This study provides a novel route for the intersection of Islam and Confucianism and highlights the potential for interdisciplinary analysis in exploring cultural intersections.